Investigation of the mechanism underlying the vasoprotective effects of red yeast rice extract in spontaneously hypertensive rats - Tan, Jiunn Jye (2024)
Hypertension is linked to endothelial dysfunction, characterized by an imbalance between relaxing and constricting factors in the vasculature. Increased activity in the renin-angiotensin-aldosterone system (RAAS) is implicated in hypertension as it leads to increased vasoconstriction and oxidative stress to cause endothelial dysfunction. Red yeast rice (RYR) is a traditional Chinese medicine that contains monacolin K, similar to statins, which have been reported to inhibit RAAS activity. To add, RYR was reported to have anti-hypertensive effects as well. Hence, the present study aimed to elucidate the vasoprotective effects of RYR through RAAS suppression by oral administration in spontaneously hypertensive rats (SHR). SHR were randomly divided into 3 groups: SHR – Control; SHR – RYR (100 mg/kg/day); SHR – lovastatin (10 mg/kg/day). Wistar-Kyoto Rats (WKY) were used as normotensive controls. All animals were treated for 12 weeks by oral gavage. Systolic blood pressure was measured weekly by tail-cuff method. Vascular reactivity was determined using isolated aortic rings in an organ bath, Aortic levels of reactive oxygen species (ROS) and nitric oxide (NO) were determined by fluorescence assays in cryostat sections of aorta, while tetrahydrobiopterin (BH4) and cyclic guanosine monophosphate (cGMP) levels were measured by enzyme-linked immunosorbent assay (ELISA). Expression of vascular angiotensin II type 1 (AT1) and type 2 receptor (AT2) were evaluated by Western blot. It was observed that administration of RYR attenuated systolic blood pressure elevation and improved ACh-induced relaxation in aortic rings, thus suggesting the involvement of the eNOS-cGMP pathway. This suggestion is further supported by the observation whereby incubation of aortic rings from untreated SHR with a combination of RYR and N-Nitro-L-arginine methylester (L-NAME) resulted in a nearly complete inhibition of relaxation of the vascular tissue. In addition, RYR decreased ROS production and AT1 receptor expression and significantly improved the levels of vascular NO, BH4, cGMP and AT2 receptor expression. These findings show that treatment with RYR extract for 12 weeks reduced the expression of AT1 receptors, leading to attenuated oxidative stress that decreases eNOS uncoupling via improving the level of BH4 and thus enhanced NO-cGMP signalling. These effects contribute to the improvement in vascular function and hence reduced systolic blood pressure observed in SHR. This study contributes new information regarding the blood pressure lowering mechanisms of RYR and its potential use as a complementary treatment for hypertension.